Adsorption and dielectric properties of poly(1-vinylimidazole) on sepiolite - ESMER, KADİR (ELSEVIER SCIENCE BV, 2012)
The adsorption of poly(1-vinylimidazole) (PVI) onto sepiolite from aqueous solutions was investigated as a function of some parameters such as pH, ionic strength, and temperature. The adsorption of PVI was increased with increasing pH and with decreasing ionic strength and temperature. The Langmuir isotherm model fitted the isotherm data better than the Freundlich model. The electrophorotic mobility of sepiolite dispersions was measured at different PVI concentrations and pH. The thermodynamic parameters Gibbs free energy, enthalpy, and entropy were evaluated. The dimensionless separation factor (R-L.) revealed that sepiolite can be used for adsorption of PVI from aqueous solutions. The second-order kinetics equation best fitted the experimental data. Dielectric properties of sepiolite coated with PVI have been also investigated. The sample with adsorbed PVI at 25 degrees C has the maximum the AC conductivity and the charge carriers can move easily in comparison with other samples. The real permittivities of the PVI-adsorbed samples are quite high in comparison with those of the pure polymer as a result of interface interactions. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Adsorption poly(1 vinylimidazole); Sepiolite; Electrical conductivity, dielectric properties; AQUEOUS-SOLUTION; DYE; KINETICS; SURFACES; BEHAVIOR; SILICA; POLYVINYLIMIDAZOLE; SORPTION; REMOVAL; MODEL